Investigation of tail pipe breakdown incident for 110 kV cable termination and proposal of fault prevention. (January 2020) - Lai, Qingbo; Chen, Jie; Hu, Libin; Cao, Jingying; Xie, Yue; Guo, Deming; Liu, Gang; Wang, Pengyu; Zhu, Ningxi
Highlights: Mechanism of discharge is analyzed by establishing 3D simulation model. Model with defects is built to analyse formation of penetrating insulation damage. Some improvement measures for the installation of cable terminations are proposed. Abstract: For cable termination, which is regarded as a key segment of power grid connecting cable lines with other electrical equipments, its insulation parts withstand much higher electric field strength than the average electric field strength of overall cable line. The excessive local electric field strength may result in the appearance of cable termination breakdown fault which can cause serious harm to the power supply reliability of whole transmission line. Historical statistics show that the breakdown location of cable termination is not confined to the vicinity of stress cone. However, the existing researches have not attached enough importance to the breakdown faults at the tail pipe of cable termination. Thus, it is of considerable significance to study the mechanism of breakdown fault at the tail pipe of cable termination. In this paper, a breakdown fault case of cable termination tail pipe on a 110 kV transmission line is investigated. Firstly, the disassembly inspection is applied to cable terminations of this fault line, and the possible breakdown reasons are preliminarily inferred. Then, a three-dimensional electric field simulation model of intact cable termination is established, and the mechanism of creeping discharge and air discharge inside the tail pipe occurred at the initial stage of breakdown fault is explained by this model. Subsequently, by setting defects on cable insulation surface in the simulation model of intact cable termination and varying the size of defects, the process of cable insulation damage inside the tail pipe formed in the initial stage developing into a penetrating cable insulation damage is simulated. Finally, the mechanism of breakdown fault case of cable termination tail pipe is concluded, and some improvement measures for the installation of cable terminations are proposed to reduce the incidence probability of such breakdown fault at the tail pipe of cable termination. The method for analyzing the breakdown fault case of cable termination tail pipe presented in this paper, which combines the disassembly inspection and simulation analysis, can provide reference and suggestions for the investigation and solution in similar cases.